Complicated Appendicitis-Shifting towards Early Appendectomy-A Comprehensive Review - Hari Rajah, Kumar; Menon, Somanathan (IIUM Medical Journal Malaysia, 2024)
The management of complicated appendicitis has undergone a transformative shift in recent years, moving away from the traditional conservative approach followed by interval appendectomy towards early appendectomy. This review article explores the current landscape of complicated appendicitis management, investigating the roles of conservative treatment, interval appendectomy, and early appendectomy. With no definitive consensus in place, the choice of treatment largely depends on the individual surgeon. The emergence of laparoscopic appendectomy has played a pivotal role in this paradigm shift, further highlighting the need to reevaluate and understand the various management options available. A total of 43 articles, 24 from Asia, 12 from Europe, 5 from the USA and 1 from Africa were retrieved from PubMed, Google scholar and the Cochrane database of clinical reviews. This review synthesizes existing literature, shedding light on the advantages and considerations associated with each approach.